The Effectiveness of Hypnotherapy in Reducing Stress, Anxiety, and Depression in People Living with HIV/AIDS (PLWHA): A Scoping Review” - Prayogo Pangestu Abadi; Anggorowati Anggorowati; Fitria Handayani (Indonesian Journal of Global Health Research, 2025)
People living with HIV/AIDS (PLWHA) may experience psychological issues such as stress, anxiety and depression. This impacts the behavior of PLWHA, who may hide their HIV status, fear taking HIV tests, and delay treatment. Hypnotherapy is one of the non-pharmacological interventions that effective for stress, anxiety and depression. Objective: to summarize or compile the effectiveness of hypnotherapy in reducing stress, anxiety, and depression in people living with HIV/AIDS (PLWHA). Method: literature sources were obtained through searches in the ProQuest, ScienceDirect, and Google Scholar databases. The articles used were articles that had been published from 2015 to 2024. The keywords used for the search included HIV/AIDS, hypnotherapy, hypnosis, depression, anxiety, and stress. A total of 5913 articles were found. The articles obtained were then analyzed according to the inclusion criteria to determine differences and duplications. A diagram for a visual representation of how the search and selection of articles was carried out is shown in the PRISMA-SR flow diagram. Data extraction was done by creating a table. Result: the researchers identified five articles related to the effectiveness of hypnotherapy in reducing stress, anxiety, and depression in people living with HIV/AIDS (PLWHA). There were several interventions, such as hypnotherapy, a combination of hypnosis with caring, and a combination of mindfulness-based spiritual cognitive therapy with hypnosis. Conclusions: all hypnotherapy interventions, as well as the combined hypnotherapy approaches, have been proven effective in reducing stress, anxiety, and depression in people living with HIV/AIDS (PLWHA).